2008
DOI: 10.1007/s11481-008-9108-4
|View full text |Cite
|
Sign up to set email alerts
|

Adaptation of Brain Glutamate Plus Glutamine during Abstinence from Chronic Methamphetamine Use

Abstract: Methamphetamine (METH) is a stimulant drug that is toxic primarily to dopaminergic and serotonergic neurons, and may lead to inflammatory changes in the brain. Additionally, the glutamatergic system is altered following METH exposure. Therefore, concentrations of brain glutamate+glutamine (GLX) were assessed during abstinence from chronic METH abuse. 25 subjects with a history of METH-dependence (age 31.8 ± 7.4 years, 14 females and 11 males) and 28 control subjects without a history of drug abuse (age 32.6 ± … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
68
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 76 publications
(72 citation statements)
references
References 40 publications
4
68
0
Order By: Relevance
“…Our study demonstrated that melatonin protects glial cells against ER stress-induced cell death. Recent studies have demonstrated that METH is a neurotoxic drug that can induce neuronal (Ajjimaporn et al, 2005;Zhu et al, 2006;Deng et al, 2007) and glial cell death by several pathways, including oxidative stress (Riddle et al, 2006;Tocharus et al, 2008), mitochondrial dysfunction (Brown et al, 2005;Jumnongprakhon et al, 2014), excitotoxicity (Staszewski and Yamamoto, 2006;Ernst and Chang, 2008), inflammatory responses (Jumnongprakhon et al, 2015), and ER stress (Shah and Kumar, 2016). We have previously reported that exposure to METH causes an overproduction of ROS (Tocharus et al, 2010) that leads to oxidative stress.…”
Section: Discussionmentioning
confidence: 99%
“…Our study demonstrated that melatonin protects glial cells against ER stress-induced cell death. Recent studies have demonstrated that METH is a neurotoxic drug that can induce neuronal (Ajjimaporn et al, 2005;Zhu et al, 2006;Deng et al, 2007) and glial cell death by several pathways, including oxidative stress (Riddle et al, 2006;Tocharus et al, 2008), mitochondrial dysfunction (Brown et al, 2005;Jumnongprakhon et al, 2014), excitotoxicity (Staszewski and Yamamoto, 2006;Ernst and Chang, 2008), inflammatory responses (Jumnongprakhon et al, 2015), and ER stress (Shah and Kumar, 2016). We have previously reported that exposure to METH causes an overproduction of ROS (Tocharus et al, 2010) that leads to oxidative stress.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the NAA/Cr ratio in the ACC is positively correlated with attentional control (Salo et al, 2007) and negatively correlated with years of methamphetamine use (Nordahl et al, 2005) among methamphetamine users, and appears to recover, albeit slowly, with extended abstinence (Nordahl et al, 2005; Salo et al, 2011). Higher levels of choline (Cho) metabolites have been found in frontal regions and the basal ganglia of methamphetamine users than non-users (Ernst et al, 2000; Nordahl et al, 2002; Nordahl et al, 2005; Sekine et al, 2002), and evidence that the level of frontal glutamate is increased (Ernst and Chang, 2008; Sailasuta et al, 2010) implicates glutamate excitotoxicity as a potential contributing factor. Inverse correlations between months of abstinence and Cho/Cr and Cho/NAA ratios in the ACC suggest that some recovery is possible after prolonged abstinence (Nordahl et al, 2005).…”
Section: Molecular Imaging Of Methamphetamine Usersmentioning
confidence: 99%
“…We are aware of only one truly longitudinal structural MRI study in psychostimulant users; it involved methamphetamine abusers over 5 months of abstinence [20]. In numerous serial studies of abstinent alcoholics, we and others showed substantial neurobiological, including structural and cognitive recovery with abstinence [4, 5, 21].…”
Section: Monosubstance Use Studies By Namementioning
confidence: 99%